Anthropometric changes in the brazilian cohort of older adults: SABE survey (Health, Well-Being, and Aging) - Almeida, Manuela Ferreira De; Marucci, Maria de Fátima Nunes; Gobbo, Luís Alberto [UNESP]; Ferreira, Luciana Silva; Dourado, Daiana Aparecida Quintiliano Scarpelli; Duarte, Yeda Aparecida de Oliveira; Lebrão, Maria Lucia (My University, 2013)
The aim of the present study was to analyze the anthropometric changes in a home-based cohort of Brazilian older adults who participated in the SABE Survey, conducted in 2000 and 2006. A total of 1030 men and women were examined by age group: 60-69, 70-79, and ≥80 years. This representative sample consists of the survivors of the 2000 cohort. The following anthropometric variables were assessed: body mass, arm muscle, waist and calf circumferences, triceps skinfold thickness, body mass index, waist-hip ratio, and arm muscle area according to mean values and percentile distribution. Except for body mass and body mass index, a significant difference (P<0.05) was observed among the assessed anthropometric variables during the follow-up period. The older adults ≥80 years presented the lowest values. The reduction in the mean values of triceps skinfold thickness was greater (30%) than that of waist circumference (9%) and was more pronounced in women (21%) than in men (9%). Arm muscle circumference and area reduced by 8% and 19%, respectively, in men and 1% and 3%, correspondingly, in women. Our findings revealed reductions in the mean values for all anthropometric variables in the follow-up period from 2000 to 2006 among older adults. © 2013 Manuela Ferreira de Almeida et al.
Keywords: adult; aged; aging; anthropometry; arm muscle; body mass; Brazil; cohort analysis; female; follow up; health survey; human; male; skinfold thickness; waist circumference; wellbeing